Potensi Lembaga Dompet Duafa dalam Optimalisasi Penghimpunan Dana Wakaf Hak Kekayaan Intelektual (HKI) - Syarifa Rahmi; Muhammad Cholil Nafis (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
Intellectual Property Rights Waqf is not new in Indonesia. This type of movable object waqf has existed for a long time but there are still many people who do not have sufficient knowledge about it. In fact, if the management of this type of waqf is maximized, it will certainly have a good impact on the economic resilience of the people who can support and advance other areas of life such as education, health and so on. The next problem is that waqf in Indonesia is still mostly managed by incompetent parties. In this regard, the author views the Dompet Dhuafa Institution as a ZIWAF fund management institution that can be said to be successful in Indonesia, both in terms of fundrising and the allocation of funds that have been collected. This is interesting to study with the aim of knowing how this institution has great potential in optimizing IPR waqf. This qualitative research uses the Dompet Dhuafa website and other literature as data sources. From this research, it can be concluded that Dompet Dhuafa is a potential institution in optimizing Intellectual Property Rights waqf funds. DD's reputation, which is well known to the wider community, has a great opportunity to spread public understanding and campaign for IPR waqf. In addition, DD has a fundrising system and well-managed programs at the central to regional levels. Funds obtained from fundrising are allocated to carry out beneficial programs that really touch the community, especially the poor, both in the fields of health, advancing the economy, education, social and religion.